(3cJGH GdCes - (3CHh YHO Gddg eMeO Hf EOQjS Hf GdYHGS Hf YKeGf Hf TGaY ,J (B204 (3g` s ((3eUQ s)
(3ChdgG (B:s
(3jHJOF HGNJdGa CHj MfjaI hGdTGaYi s
(3BNQgG (B:s
(3jfJgi HGNJdGa eGdc hGdTGaYi hgh BNQ GdcJGH s
(3GdfSNI HgG MhGTs
(3cJHJ HQSe NRGfI GdCejQ GdebOe GdCejf GdCSagSdGQ GdeXaQs
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B26 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B32s
Keywords: (3Gdabg GdTGaYjs